Algunos usos del conflicto en Israel-Palestina en Argentina. Debates en torno al conflicto árabe-israelí entre el tercer peronismo y la última dictadura militar (1973-1983) - Emmanuel Nicolás Kahan (Nuevo mundo - Mundos Nuevos, 2014)
The research proposed here will consider the impact and the reception that the Arab-Israeli conflict has had within the frame of a series of particularly controversial superimposed contexts: the "Iom Kipur" War (1973) and the "First Lebanon War" (1982).The impact and reception of these two wars took place during a  particularly sensitive historical period in Argentina: between the return of Peronism to power and the last Argentinean dictatorship (to the extent that the Lebanon War started just a few days before the Malvinas war ended).